KAJIAN OPTIMASI PEMANFAATAN EMBUNG PAYA SEPAT UNTUK MEMENUHI KEBUTUHAN AIR IRIGASI D.I. CUBO TRIENGGADENG ZONA III KABUPATEN PIDIE JAYA - Ivan Mirza; Ella Meilianda; Azmeri Azmeri (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
The Cubo Trienggadeng Irrigation scheme has a potential area of 1,545 Ha while the functional area is 1,090 Ha. Based on the Irrigation Network scheme, Cubo Trienggadeng Irrigation Area consists of 3 (three) zones: Zone I, Zone II and Zone III. In Zone III of the Cubo Trienggadeng Irrigation Area which is the latest area receiving water from the Cubo Trienggadeng Weir often occurs in water shortages especially during the Gadu planting season (second planting season). Paya Sepat irrigation is the reservoir found in Zone III D.I. Cubo Trienggadeng that is not being fully optimized in use. This study aims to optimize the utilization of Paya Sepat Reservoir so that it can meet irrigation water demand in Zone III D.I Cubo Trienggadeng by using the Water Balance method. This reservoir does not have a channel that supplies inflow discharge, so rainwater harvesting becomes a parameter in analyzing the supply of water to the reservoir. The optimization technique used uses a non-linear program using the Solver facility in Microsoft Excel software. Based on the results of the calculation of irrigation water requirements for an area of 204.50 Ha in the Gadu planting season, the maximum volume of irrigation water demand is 40,461.55 m3 at the first period in June, from the results of the optimization using the Maximize Release method, the results show that the water reservoir in Paya Sepat Reservoir can meet the water requirements in the Gadu planting season with an average reliability of 100%. Therefore, it is necessary to regulate the release of irrigation water that is well regulated and coordinated between the reservoir management and water users/farmers.